Cultural Complexities and their Environment: Investigations of Code–Switching in Contemporary Visual Arts - Zoltán Somhegyi (Eidos. A Journal for Philosophy of Culture, 2023)
Contemporary artworks are primary sources for a better understanding of the most important issues in our current reality. The complexities of cultural interactions are often thematized in pieces of art using the artistic means of code-switching, and where the investigation of these questions is pursued in and with regards to the issues of the broader context, including the built and the urban setting. In this paper I examine some aspects of these questions, with the help of some inspiring examples, through artworks by creators coming from five different parts of the world: hence in the works by Manit Sriwanichpoom, Nandipha Mntambo, Michael Rakowitz, Yinka Shonibare, and Marja Helander. In this way I aim to emphasize the global relevance of these issues, as well as what we can thus learn from and about our own origins, current standpoints, and further possibilities.